Changes in disability, self-rated health, comorbidities and psychological wellbeing in community-dwelling 75–95-year-old cohorts over two decades in Helsinki. (3rd July 2017) - Karppinen, Helena; Pitkälä, Kaisu H.; Kautiainen, Hannu; Tilvis, Reijo S.; Valvanne, Jaakko; Yoder, Käthe; Strandberg, Timo E.
Abstract: Objective: To explore changes in self-reported disabilities, health, comorbidities and psychological wellbeing (PWB) in aged cohorts over two decades. Design, setting and subjects: Cross-sectional cohort studies with postal surveys were conducted among community-dwelling people aged 75, 80, 85, 90 and 95 years in 1989 ( n = 660), 1999 ( n = 2598) and 2009 ( n = 1637) in Helsinki, Finland. Main outcome measures: Self-reported items on disability, self-rated health (SRH), diagnoses and PWB were compared between cohorts of the same age. Standardized mortality ratios (SMRs) were calculated for each study year to explore the representativeness of the samples compared to general population of same age. Results: A significantly lower proportion of the 75–85-year-olds of the later study years reported going outdoors daily, although this group had improvements in both SRH and PWB scores. The number of comorbidities increased over time among 75–85-year-olds. The only significant change that could be verified among 90- and 95-year-olds between 1999 and 2009, was the lower proportion of participants going outdoors daily. The trend of leveling-off in disabilities was not explained by the SMRs (0.90, 0.71 and 0.60 for 1989, 1999 and 2009). Conclusions: The latest older people's cohorts showed an end to previously reported improvements in disabilities, despite having favorable trends in SRH and PWB. Primary care may be faced with increasing need of appropriate services for their senior members.